A comparative analysis of chemically induced sex reversal in teleosts: challenging conventional suppositions. Issue 1 (29th November 2011) - Senior, Alistair M; Nakagawa, Shinichi
Abstract Environmental sex reversal (ESR) occurs when extreme environmental factors overpower predetermined sexual development. Scientific theory is beginning to acknowledge the potential roles of sex‐reversed individuals in influencing population dynamics and driving the evolution of sex‐determination mechanisms. ESR is a phenomenon that has been widely observed in fish and can be induced by exposing individuals to exogenous hormones. However, reports of the susceptibility of fish to hormonally induced ESR vary greatly – a concept we termed 'inducibility'. It has been suggested that variation in inducibility can be attributed to biological differences among species of different taxonomic groups (i.e. phylogenetic effects are present). Here, we provide the first quantitative test of this theory, which was achieved by combining published data with phylogenetic trees, using phylogenetically controlled comparative analysis. Our results confirm that a great amount of variation exists in the reported inducibility of fish. However, species and taxonomic relationships were responsible for trivial portions of variation. Rather, we found that sampling (measurement) errors in combination with methodological differences across studies accounted for much more variation in inducibility than taxonomy did. Given that our analysis contains representatives from over 25% of all teleost orders, we conclude that inducibility is not a taxonomically constrained trait in teleosts. Therefore, we suggest that the sex‐determination mechanisms of most fish are uniformly plastic. Further, we propose that ESR occurs relatively regularly over evolutionary time in many teleost species, playing a vital role in the maintenance of homomorphic sex chromosomes in this taxonomic group.